2006
DOI: 10.1089/ten.2006.12.2863
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Osteogenic Differentiation of Rat Bone Marrow Stromal Cells in Thermosensitive MPEG–PCL Diblock Copolymer Gels

Abstract: Methoxy poly(ethylene glycol)-poly(epsilon-caprolactone) (MPEG-PCL) diblock copolymers were prepared by ring-opening polymerization and their phase transition behavior characterized as a function of temperature. The MPEG-PCL solutions formed a sol at room temperature, and underwent sol-to-gel followed by gel-to-sol phase transitions as the temperature was increased. The temperature range over which the solutions were in a gel state could be extended simply by increasing the PCL chain length in the diblock copo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 35 publications
0
42
0
Order By: Relevance
“…[104] Histological analysis demonstrated that in situ formed MPEG-PCL hydrogels containing rBMSC and dexamethasone were biocompatible and enhanced bone formation. The in vitro release of FITClabeled bovine serum albumin (FITC-BSA) from the MPEG-PCL hydrogel showed a sustained release profile for more than 20 days.…”
Section: Temperature-sensitive Block Copolymer Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…[104] Histological analysis demonstrated that in situ formed MPEG-PCL hydrogels containing rBMSC and dexamethasone were biocompatible and enhanced bone formation. The in vitro release of FITClabeled bovine serum albumin (FITC-BSA) from the MPEG-PCL hydrogel showed a sustained release profile for more than 20 days.…”
Section: Temperature-sensitive Block Copolymer Hydrogelsmentioning
confidence: 99%
“…PLGA Chondrocyte MPEG-PCL rBMSC, dexamethasone [104] FITC-BSA, BSA [105,106] Cholesterol end-capped star PEG-PLLA L929 cells [46] PEG/PPG/PHB BSA [48] Polyphosphazenes FITC-dextran, HSA [107] Doxorubicin, paclitaxel [108,112] FITC-albumin [109] Pancreatic islets, hepatocytes [110,111] C/GP Camptothecin, insulin [113,114] Bovine chondrocytes [115] pH/temperature-sensitive OSM-PCLA-PEG-PCLA-OSM Paclitaxel [116] hMSCs [117] PAE-PCL-PEG-PCL-PAE Insulin [82,118] (PCL-PEG-PCL-PAU) n Paclitaxel [86] (PEG-PAU) m Chlorambucil [87] PAA-PEG-PAA Flurbiprofen [90] PAE-PEG-PAE Lidocaine [89] matrices or cell growth depots. Table 1 summarizes the biomedical applications of the biodegradable injectable hydrogels.…”
Section: Hydrogel Types Polymer Delivery/applications Referencesmentioning
confidence: 99%
“…Some of the implants were separated from the bone, washed, fixed and embedded in paraffin. Hematoxylin-eosin and Von Kossa stained sections (5 mM thick) were prepared from samples of bone+implant and implants alone [26]. For immunostaining of eGFP expressing cells, tissue sections were deparaffinized, rehydrated and washed in PBS.…”
Section: Histology and Immunostainingmentioning
confidence: 99%
“…The underlying physical gelation happens due to formation of percolated micelle network [51e55]. The resulting hydrogels are promising as drug delivery carriers [44,56] and tissue engineering materials [57,58]. The corresponding gel surface is rich of PEG segments which resists nonspecific protein absorption and cell adhesion, so cells could not adhere on these hydrogels well.…”
Section: Introductionmentioning
confidence: 99%